Предмет: Алгебра,
автор: temergalinavaa
6-3-y =y-1+y-2
2 2 3
Ответы
Автор ответа:
0
Автор ответа:
0
6 - (3-y)/2 = (y-1)/2 +(y-2)/3 приводим к общему знаменателю
(6*6-3(3-y))/6 = (3(y-1))+2(y-3))/6 знаменатель сокращаем, скобки раскрываем
36-9+3y = 3y-3+2y-6
36-9 +3y = 5y -9
36 =5y-3y =2y
y =26/2 =18
y=18
(6*6-3(3-y))/6 = (3(y-1))+2(y-3))/6 знаменатель сокращаем, скобки раскрываем
36-9+3y = 3y-3+2y-6
36-9 +3y = 5y -9
36 =5y-3y =2y
y =26/2 =18
y=18
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: apelsinarbuzovic
Предмет: Алгебра,
автор: vityamath
Предмет: Алгебра,
автор: anvik77
Предмет: Биология,
автор: GalaiAnton